Long-Term Performance of Malaysian Horizontal Mergers and Acquisitions - Aik, Naik Chiek (2010)
This study examines the long-term performance of Malaysian horizontal M&A activities. Four different measures were applied to ascertain whether the expected long-term economic gains are actually realized following the M&As. The findings indicate that the effects of M&A on bidder firms are negative in the long run. In particular, the operating performance of bidder firms deteriorated in the period after merger, while that of nonmerging rivals to bidder firms improved over the same period, suggesting a spillover effect. For target firms, the findings suggest no synergistic gains in operating performance after M&A activities. These findings are consistent with the findings of financial analysis for the same sample to ascertain results from the non-use of traditional method in M&A literature. The sub-period analysis however revealed that M&A activity improves the operating performance of matching firms only for a very short run specifically in a year after M&A. In fact, the operating performance of major competitors (both bidder and non-merging rival firms) deteriorates in the long run, most notably in all years after year three of M&As. The findings on industry effect reveal that M&A activity diminishes operating performance of bidder firms in manufacturing industry and matching firms in construction industry, suggesting that horizontal M&A activity in these industries (which rely heavily on the manpower) is not advantageous to improve operating performance of bidder firms and non-merging rival firms in Malaysia. Consistent with the literature, the findings showed no significant change in technical efficiency of the merging firms after M&As. Similar findings are documented for the matching firms despite the insignificant declines in technical efficiency of matching firms are lower compared to bidder firms. Bidder firms however show a significant decline in cost efficiency in the long run, particularly within two specific window periods of three years before and three years after, and three years before and all years after year three of M&As. The findings show a significant improvement in productivity of merging firms and nonmerging rival firms in the long run. Similar to the bidder firms, productivity growth of non-merging rival firms is mainly due to the technical change (frontier shift effect) despite their higher level of technological progress compared to the bidder firms. Productivity of target firms, on the other hand, is solely contributed by the efficiency change (catching up effect).